Motivation Interview Effectiveness and Optimism Efficiency on the Quality of Life of Type 2 Diabetes Mellitus - Amiruddin, Ridwan; Jafar, Nurhaedar; Ansar, Jumriani; Tasya, Zhanaz (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This study aims to analyze the quality of life of people with type 2 diabetes mellitus (T2DM) through the intervention of motivational interview and efficacy of optimism. METHODS: The type of research is Quasi Experimental - Non-Randomized Control Group Pretest Posttest Design. The sample was T2DM patients, while the treatment was carried out on 50 respondents. Interventions were given in motivational interviews and the effectiveness of optimism. The statistical test used is the two-dependent difference test and two independent mean difference test. RESULTS: The statistical test of the difference between the two independent means showed the sig. value (two tailed) of 0.006. It pointed to a significant difference in post-test between DM patients’ quality of life in the intervention and control groups. Based on the two dependent difference test, the mean showed that the value of sig. (two tailed) 0.000 means a significant difference between DM patients’ quality of life in the intervention and control groups after the post-test. CONCLUSION: There was a substantial relationship between motivational interviewing and optimism efficacy on the quality of diabetes mellitus patients.